Building Public Accountability Through Financial Management in Madrasah - Riinawati, Riinawati (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aimed to describe the application of educational and financial management in planning, implementation, evaluation, and financial accountability of education at MAN 1 Banjarmasin. The method used in this research is a qualitative method with a descriptive analysis approach, namely research that describes what is happening in a particular field, field, or area. The data collection techniques used observation, interviews, and documentation studies. The sources of information in this study were the head of the madrasah, the treasurer of the madrasah, the head of administration, and the staff of the madrasah treasurer. The results showed that financial management implementation at MAN 1 Banjarmasin was carried out very well. The management process begins with the planning, implementation, evaluation, and accountability processes. Financial evaluation and accountability are carried out routinely orally and in writing through working meetings, coordination meetings, and reports through online connected applications. All reports on the use of funds are accountable to the government through the Ministry of Finance.